DIFFERENCES OF APPROACH INFLUENCE ON LEARNING AND MOTORIC SKILLS TOWARDS TOP SPIN SERVICE LEARNING OUTCOMES OF VOLLEY BALL - WIDAGDO, WIDAGDO; HUTOMONO, SHODIQ (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2019)
Widagdo, NIM: E 0117019, 2019, DIFFERENCES OF APPROACH INFLUENCE ON LEARNING AND  MOTORIC   SKILLS TOWARDS TOP SPIN SERVICE LEARNING OUTCOMES OF VOLLEY BALL. Thesis: The Major of Pendidikan Jasmani, Post Graduate Tunas Pembangunan University Of Surakarta. ( Study Experiment About Teaching Approach With Dirrect Approach and Indirrect Approach At College Student Sport Training Program, Faculty Teacher Training And Education. Tunas Pembangunan University ). Thesis: Study Program of Sports Education, Postgraduate Program, Tunas PembangunanUniversity of Surakarta The aims research of the are to investigated: (1) The different effect of teaching approach with direct approach and indirect approach to learning result volleyball  stop spin service. (2) The different the learning result volleyball top spin service  skill between college student group having high motoric  ability and motoric  ability lower. (3) Interaction effect of usage of teaching approach and motoric  ability to learning result  volleyball top spin service skillExperiment method with 2 X 2 factorial design was used in this research.  The Research Population is the male college student of Sport Training Program, Faculty Teacher Training And Education, Tunas Pembangunan University Surakarta, Central Java Academic Year 2018/2019 i.e. 60 college students. Sampling technique was used purposive random sampling,, the amount of sample taken are 40 college students. Sample consists of 20 college student represent owning high hand-eye coordination and 20 college students owning low hand-eye coordination. The variable that researched is independent variable consist of two factor that were manipulative variable, attributive variable, and also one (1) dependent variable. Manipulative variable consist of the teaching approach with the direct approach and indirect approach. Attributive Variable consists of groups with high motoric  ability and low motoric  ability. (2) Dependent variable in this research is volleyball top spin service. Data collecting technique are test and measurement. The data collecting of  volleyball games skill is using underhand service and under hand passing test. Data of motoric  ability done using throw and catch tennis ball. Data analysis Technique in this research use analysis of variance test and span Newman Keuls, at 5% level of significance.Conclusion: (1) There is a significant different of effect which between teaching approach with direct approach and indirect approach to learning result volleyball top spin service. The  effect teaching approach with the direct approach is better than  with the indirect approach. (2) There is learning result volleyball top spin service different a significant between college student group owning high motoric  abilty and motoric  ability lower to. Uplifting of volleyball top spin service at college student owning high motoric  ability is better than those who owning low motoric  ability. (3) There is a significant of interaction effect between usage of teaching approach and motoric  ability to learning result volleyball top spin service. (a) College student having high motoric  ability more compatible if given by teaching with the direct approach. (b) College student motoric  ability lower more compatible if given by teaching with the indirect approach